Are You a Ladybug? - Allen, Judy; Nang ChanYeema (New York, USA Kingfisher Books, 2000)
Introduces the life cycle of a ladybug, showing how it changes from egg to an adult ladybug.
Keywords: Juvenile Nonfiction